Pengaruh Smartphone terhadap Perilaku Agresif Anak Usia SD di Dusun Gondanglegi Pada Masa Pandemi - Maemonah Maemonah; Aisyah Sabilla Rahmi (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the impact of smartphone use on the aggressive behavior of elementary school-aged children in Gondanglegi Hamlet during the pandemic. Employing a quantitative approach, structured questionnaires were distributed to 20 children in Gondanglegi Hamlet. The determination of indicators for smartphone uses and aggressive behavior was based on the latest literature, introducing a novel perspective in the research focus. Regression analysis indicated that smartphone usage significantly influences aggressive behavior. Key findings highlight that the most dominant aggressive behaviors resulting from smartphone usage include envy, insults, pushing, and anger. However, a supportive environment can mitigate the adverse effects of smartphone use. These findings are crucial as they provide insights into the behavioral changes in children during the pandemic and serve as a cautionary note for educators and parents to intensify supervision of smartphone use by children. Recommendations from this study are hoped to assist educators and parents in overseeing children's smartphone use.